(untitled) (IMC Journal of Medical Science, 2019)
Background and objectives: Low vitamin D is a global problem in all age groups as is osteoporosis in postmenopausal women. The present study was carried out in an urban hospital to assess serum 25-hydroxyvitamin D [25(OH)D] level and bone mineral density (BMD) in postmenopausal women (PMW) and to evaluate correlation between serum 25(OH)D levels and BMD. Methods: A single center cross-sectional study was conducted among 133 apparently healthy PMW aged 45 years and above with the history of complete cessation of menstruation over a period of more than 1 year. Serum 25(OH)D, BMD and serum intact parathyroid hormone (iPTH) were determined. Patients having both vitamin D and BMD values were analyzed for correlations. Similarly, correlation of vitamin D, iPTH and BMD were determined. Results: Among the study population, 63 (47.4%) had deficient (<20 ng/ml), 46 (34.6%) had insufficient (20-30ng/ml) and 24(18%) had sufficient (30-100ng/ml) levels of serum 25(OH)D. Among the 121 patients whose BMD was done, 52 (43.0%) and 60 (49.6%) had osteoporosis and osteopenia respectively. Serum iPTH levels were normal in 34 (89.5%) patients. The proportion of osteopenia and osteoporosis in vitamin D deficient group were 44.1% and 50.8% and in insufficient group 47.5 and 45.0%, respectively. Age had significant negative correlation with BMD value (r=-0.246, p=.005) and significant positive correlation with serum iPTH (r=0.358, p=.024). There was no statistically significant influence of serum 25(OH)D or iPTH on occurrence of osteoporosis (P=0.322 and P=0.592 respectively). Conclusion: A large proportion of postmenopausal women had low vitamin D levels and as well as osteopenia and osteoporosis. Low vitamin D level coexisted with low BMD. However, there was no correlation between serum 25(OH)D levels and BMD status. IMC J Med Sci 2018; 12(2): 44-49